TINGKAT PENGETAHUAN IBU TENTANG PENTINGNYA PERSALINAN DITOLONG TENAGA KESEHATAN DI DUSUN PALELENG DESA KASERALAU KECAMATAN BATULAPPA KABUPATEN PINRANG TAHUN 2018 - Dewi Purnama Windasari (LPPM STIK Makassar, 2018)
Labor is a very complex thing because there is happiness happening before the birth ofchildren but there are risks that may threaten the safety of mother and baby. MaternalMortality Rate (MMR) in Indonesia is still quite high. Based on Indonesia Demographic andHealth Survey (SDKI) in 2015, coverage of labor by health personnel is about 90.88%, whichmeans that there are still 10% labor that is not helped. While data of RISKESDES year 2015indicate that delivery done at home still high enough that is equal to 29,6%. At DusunPaleleng Kaseralau Village Batulappa Subdistrict Pinrang District in the year 2017 inAugust there are 8 childbirths or (34.8%) whose delivery is not helped by health workersfrom a total of 23 Pairs of Age of Fertile or (100%). Based on the result of activity ofknowledge level on prenatal test assisted by health personnel there are 16 people (100%),who know with 7 people (43.8%) while those who do not know 9 people (56.2%), after theextension then the result of knowledge level on post test of labor assisted by health personnelthere are 16 people (100%), who know with the number of 16 people (100%).